2022
DOI: 10.1021/acs.biomac.1c01396
|View full text |Cite
|
Sign up to set email alerts
|

Truly Multicolor Emissive Hyperbranched Polysiloxane: Synthesis, Mechanism Study, and Visualization of Controlled Drug Release

Abstract: Unconventional fluorescent polymers have attracted increasing attention due to their facile synthesis, excellent biocompatibility, and novel photophysical properties. In this work, a truly multicolor emissive hyperbranched polysiloxane (HBPSi-β-CD) is obtained through adjusting the distribution of electron-rich atoms and grafting β-cyclodextrin; the quantum yields of HBPSi-β-CD after being excited by 360, 420, 450, and 550 nm are 19.36, 31.46, 46.14 and 44.84%, respectively. The density functional theory calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Yan et al found that the electron cloud of carbonyl and CC bonds in polysiloxane will overlap and form multiple through-space conjugation rings, and blue, green, and red light will be generated under different excitations; hence, the emission mechanism named multiring-induced multicolor emission is proposed . We found that the electronic communication between electron-rich functional groups could be promoted through decreasing the distance and steric hindrance and then generate large spatial electronic delocalizations, and finally, bright blue, green, yellow, and red emissions are observed . These research studies show that the long-wavelength emission of polymers is closely related to the species of functional groups, density of electron-rich atoms, interactions between functional groups, morphologies of aggregates, and so on.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Yan et al found that the electron cloud of carbonyl and CC bonds in polysiloxane will overlap and form multiple through-space conjugation rings, and blue, green, and red light will be generated under different excitations; hence, the emission mechanism named multiring-induced multicolor emission is proposed . We found that the electronic communication between electron-rich functional groups could be promoted through decreasing the distance and steric hindrance and then generate large spatial electronic delocalizations, and finally, bright blue, green, yellow, and red emissions are observed . These research studies show that the long-wavelength emission of polymers is closely related to the species of functional groups, density of electron-rich atoms, interactions between functional groups, morphologies of aggregates, and so on.…”
Section: Introductionmentioning
confidence: 58%
“…UV–vis absorbance was first studied to confirm the presence of heterogeneous special electronic delocalizations in the aggregates of polymers. In the UV–vis absorbance spectra of HBPSi (Figure a), a peak at 208 is observed, which is caused by the n−σ* electronic transitions of hydroxyl, −Si­(O) 3 , and amine groups. , Different with the UV–vis absorbance spectra of HBPSi, new absorbance peaks at about 269, 340, 400, 450, and 500 nm in the UV–vis absorbance spectra of HBPSi-Phe (Figure b), HBPSi-Tyr (Figure c), and HBPSi-Trp (Figure d) are also observed at concentrated solutions, and these new peaks are enhanced with increasing concentrations. The absorbance at 269 nm might come from the π–π* electronic transitions of the conjugated π bonds in the amino acids (Figure S3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…23−26 Yan et al synthesized a multicolor emissive hyperbranched polysiloxane (HBPSi) that they applied to detect metal ions and use as a nanocarrier; it exhibited multicolor fluorescence because of CIE and its cluster size. 27 Interestingly, Yang et al used thiolactone chemistry to synthesize aliphatic polyamides (PAs) that could produce strong fluorescence as a result of polymerization-induced emissions (PIEs); 28 these aliphatic PAs were applied to organelle-specific imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The nonconventional fluorescence observed with nonconjugated moieties can lead to strong fluorescence emissions with excellent photostability because of resistance to photobleaching and nonquenching effects. , Furthermore, nonconjugated HBP nanomaterials featuring multiple hydrogen-bonding interactions can have chemical structures similar to those of biopolymers, with excellent water solubility, chain flexibility, and structural tunability as well as the potential for facile one-pot preparation, environmental friendliness, and use in biological fluorescence imaging. Nonconventional fluorescent polymers have been applied in various applications, including the detection of metal ions, bioimaging, and nanodrug formulation. Yan et al synthesized a multicolor emissive hyperbranched polysiloxane (HBPSi) that they applied to detect metal ions and use as a nanocarrier; it exhibited multicolor fluorescence because of CIE and its cluster size . Interestingly, Yang et al used thiolactone chemistry to synthesize aliphatic polyamides (PAs) that could produce strong fluorescence as a result of polymerization-induced emissions (PIEs); these aliphatic PAs were applied to organelle-specific imaging.…”
Section: Introductionmentioning
confidence: 99%